Changes in Air Quality during the COVID-19 Lockdown in Singapore and Associations with Human Mobility Trends - Jiayu Li; Federico Tartarini (Aerosol and Air Quality Research)
Abstract On the 7th of April, the Singaporean government enforced strict lockdown measures with the aim of reducing the transmission chain of the coronavirus disease 2019. This had a significant impact on the movement of people within the country. Our study aims to quantify the impact that these measures had on outdoor air pollution levels. We obtained air quality and weather data from April 2016 to May 2020, satellite data for 2019 and 2020 and mobility data for 2020 from Apple, Google, and the Singaporean Housing & Development Board. We determined that outdoor air pollution during the lockdown significantly decreased when compared with the same period in the previous four years even if we included corrections for long time trends in the analysis. The concentrations of the following pollutants PM10, PM2.5, NO2, CO, and SO2 decreased by 23, 29, 54, 6, and 52%, respectively, whilst that of O3 increased by 18%. The Pollutant Standard Index decreased by 19%. The trends of PM2.5 and NO2 were significantly correlated with mobility data. The NO2 and SO2 tropospheric concentrations and the total aerosol optical depth at 550 nm obtained from satellite data during the lockdown in 2020 were also lower than during the same period in 2019. Our results can be used to evaluate possible mitigation strategies for outdoor air quality in a longer term beyond this lockdown.